The really useful science book : a framework of knowledge for primary teachers - Farrow, Steve (London : Routled Falmer Press, 2005)
The Really Useful Science Book has been written with primary classroom teachers and teachers in training in mind. It has been designed to support and extend teachers' and student's own knowledge and understanding of science and should be of particular interest to those primary practitioners who see themselves as 'non-specialists'. Throughout the book every effort has been made to interpret the ideas and concepts.
Include index.
Keywords: Science -- Study and teaching (Elementary) -- Great Britain; Education, Elementary -- Curricula -- Great Britain; Science -- Étude et enseignement (Primaire).